SALES PREDICTION AT PT. GILANG PRATAMA USING THE MONTE CARLO SIMULATION METHOD - Manurung, Jonson; Sihotang, Amran; Ramen, Sethu; Logaraj, Logaraj (INFOKUM, 2022)
Simulation can help solve everyday problems such as problems that exist at PT. Gilang Primary. With a simulation application that can estimate the number of sales is very important for the company. If the manager can predict the number of sales, the cost of procuring and storing goods can be minimized. One approach that can be taken to estimate the number of sales is by way of simulation. This study uses the Monte Carlo method in managing data and analyzing inventory or determining the amount of goods to be sold in the next period at PT. Gilang Pratama with sampling from the process of random numbers (Additive Random Number). Data processing uses sample data based on sales history data in the previous year